Perceptions, practices, and experiences of asthma patients and community pharmacists on short-acting beta-2 agonists inhaler use: A qualitative study - Rabia Hussain; Zhe Chi Loh; Bayan Faisal Ababneh; Jaya Muneswarao; Siew Chin Ong; Bandana Saini; Anees ur-Rehman; Vibhu Paudyal (Journal of Pharmaceutical Policy and Practice)
Background Short-acting beta-2 agonists (SABA) are bronchodilators that offer rapid relief for asthma patients experiencing acute symptoms. The availability of SABA inhalers without a prescription may exacerbate the overuse of SABA. This study aimed to explore the perceptions, practices, and experiences of asthma patients and community pharmacists toward using SABA inhalers in Malaysia.Methods A qualitative study was conducted among eleven asthma patients and twelve community pharmacists using semi-structured individual interviews. All interviews were audio-recorded and transcribed verbatim and then analyzed by thematic analysis. The findings were reported using the COREQ checklist.Results Thematic analysis yielded eight major themes, (1) perceptions and understanding of good asthma control; (2) perceptions and experience towards asthma follow-up review; (3) perceptions of SABA’s reliance; (4) practices towards the proper use of inhalers; (5) over-the-counter availability of SABA inhalers; (6) provision of pharmacists in SABA use assessment; (7) patients-healthcare professionals communication; and (8) recommendations for policymakers.Conclusion Most asthma patients and community pharmacists agreed that good asthma control was associated with reduced SABA usage and minimum asthma symptoms. The majority of patients claimed that visiting physicians for asthma follow-up reviews was unnecessary. Moreover, community pharmacists have raised concerns regarding patients’ reliance on SABA inhalers due to the immediate relief effects, however, the majority of interviewed patients claimed that they did not rely on SABA inhalers. Additionally, community pharmacists were generally concerned about the frequency, dosage, and techniques using SABA inhalers. These concerns need to be addressed to improve the safe use of SABA inhalers. Language barriers, health literacy, long waiting times, and public education were the most important believed determinants of the safe use of SABA inhalers.